Environment-friendly anion gypsum plaster board and preparation method thereof
By adding negative ion powder, silicone powder and improved foaming agent to paper gypsum board, combined with the use of titanium dioxide, the problem that existing paper gypsum board cannot effectively adsorb indoor formaldehyde, effectively adsorbing formaldehyde and air purification are achieved, and the environmental protection performance and service life of gypsum board are improved.
Patent Information
- Application Number
- CN202411820969.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
AI Technical Summary
Existing paper-surfaced gypsum board cannot effectively absorb formaldehyde in indoor air, affecting indoor air quality.
By adding negative ion powder, silicone powder and improved foaming agent to paper gypsum board, combined with the use of titanium dioxide, a dense void structure is formed to fully absorb formaldehyde and absorb fine particulate matter in the air through electrostatic action.
It has achieved that paper gypsum board can not only effectively adsorb its own formaldehyde, but also adsorb formaldehyde in indoor air, improve air quality, and improve the environmental performance and service life of gypsum board.
Smart Images

Figure BDA0005183097600000091 
Figure BDA0005183097600000101 
Figure BDA0005183097600000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of gypsum board, in particular to an environmentally friendly negative ion gypsum board and a preparation method thereof. Background Art
[0002] Gypsum board is made of building gypsum as the main raw material, with appropriate amount of additives and fiber as the board core, and special board paper as the surface. It is processed into a board with the characteristics of light weight, sound insulation, heat insulation, strong processing performance and simple construction method.
[0003] Negative ions are negatively charged gas ions in the air. They can not only promote the synthesis and storage of vitamins in the human body, but also strengthen and activate the physiological activities of the human body. They also have a very important impact on the life activities of the human body and other organisms. Therefore, they are also called "air vitamins". As people pay more attention to environmental protection and health, the demand for functional gypsum boards is increasing.
[0004] In indoor decoration, there are some harmful gases in the decorated indoor space, especially formaldehyde, which is the most harmful to the human body and has the longest incubation period. The existing paper-faced gypsum board mainly purifies its own formaldehyde, and cannot adsorb formaldehyde in the indoor air, resulting in that the indoor formaldehyde cannot be volatilized quickly, affecting physical and mental health, while negative ions can adsorb harmful substances such as particulate matter, bacteria, and viruses in the air. When negative ions contact formaldehyde molecules with positive charges, the negative ions will combine with the positive charges in the formaldehyde molecules to form a stable complex. This complex is no longer irritating and harmful, thereby achieving the effect of removing formaldehyde, and reducing the concentration of harmful substances in the air, improving the indoor air quality. For this reason, the present invention proposes an environmentally friendly negative ion paper-faced gypsum board, which not only controls the formaldehyde of the paper-faced gypsum board itself, but also effectively adsorbs formaldehyde in the air. Summary of the invention
[0005] The purpose of the present invention is to provide an environmentally friendly negative ion paper-faced gypsum board and a preparation method thereof. The present invention can effectively release negative ions and effectively absorb formaldehyde in the air, thereby improving the environmental performance of the paper-faced gypsum board.
[0006] The technical scheme of the present invention is as follows: an environmentally friendly negative ion paper-faced gypsum board, the negative ion paper-faced gypsum board comprises a core material and a face paper, and the core material formula is calculated by weight components: it is prepared from 60-70 parts of semi-hydrated gypsum, 10-15 parts of fly ash, 10-15 parts of silica gel, 5-10 parts of negative ion powder, 5-10 parts of titanium dioxide, 0.05-0.2 parts of improved foaming agent, 0.1-0.5 parts of water reducer, 1-2 parts of retarder, 2-5 parts of plant starch, 2-3 parts of activated rubber powder and 40-50 parts of water.
[0007] The aforementioned negative ion powder is tourmaline powder.
[0008] The improved foaming agent is composed of ethoxylated sodium alkyl sulfate, sodium α-olefin sulfonate, sodium xylene sulfonate and a foam stabilizer in a weight ratio of 1-2:1-2:0.5-1:0.05-0.2; the foam stabilizer is composed of fatty acid monoethanolamide and fatty alcohol polyoxyethylene ether in a weight ratio of 1-2:1-2.
[0009] The water reducing agent is composed of melamine and calcium lignin sulfonate in a weight ratio of 1-2:5-10.
[0010] The aforementioned retarder is composed of sodium citrate and malic acid in a weight ratio of 1-5:1-5.
[0011] The plant starch is one or more of wheat starch, corn starch and potato starch, and the particle size of the plant starch is 80 to 300 meshes.
[0012] The preparation method of the aforementioned environmentally friendly negative ion paper-faced gypsum board is carried out according to the following steps:
[0013] (1) Grinding the fly ash through a grinder and passing it through an 80-mesh sieve to obtain fly ash powder for later use;
[0014] (2) Preparation of activated rubber powder: Add putty rubber powder to 10% sodium carboxymethyl cellulose solution and react for 24h-48h, filter to obtain pretreated rubber powder, then add 1% aqueous aziridine crosslinking agent and stir evenly, react for 0.5-1.5h to obtain activated colloid, wash with water, dry at 65°C, crush through a 100-mesh sieve to obtain activated rubber powder, and set aside;
[0015] (3) taking silica gel, soaking it in dilute nitric acid at a volume ratio of 1:1 for 10-12 hours, then washing it with water until it is neutral, then soaking it in dilute hydrochloric acid at a volume ratio of 1:1 for 5 hours with shaking, then washing it with water until it is neutral, washing it with acetone to remove organic impurities, filtering it, drying it at 150-160° C. for 3 hours, grinding it to powder and passing it through a 100-mesh sieve to obtain silica gel powder for later use;
[0016] (4) After grinding the semi-hydrated gypsum through an 80-mesh sieve, add fly ash powder and silica gel powder, stir evenly, add water and stir to form gypsum slurry to obtain product A, which is set aside;
[0017] (5) Take the improved foaming agent and half the amount of water in the formula and mix them evenly to obtain Product B, which is set aside;
[0018] (6) Mix the retarder, plant starch and activated rubber powder with half the amount of water and stir evenly to obtain product C, which is set aside;
[0019] (7) Add titanium dioxide, water reducing agent, product B, and product C to gypsum slurry A in sequence, stir evenly to obtain gypsum slurry, and set aside;
[0020] (8) After the upper and lower papers are unwound, they enter the molding machine through an automatic deviation correcting machine. Negative ion powder is added to the gypsum slurry in the mixer before entering the molding machine, and the gypsum slurry falls onto the lower paper on the vibrating platform and enters the molding machine, where the gypsum board is extruded;
[0021] (9) The formed gypsum board is solidified on the transport track and cut into gypsum board by a cutting machine. The cut gypsum board is sent to a dryer for drying to obtain negative ion gypsum board.
[0022] In the above step (7), the stirring speed is 200-400 rpm and the stirring time is 30-40 min.
[0023] In the aforementioned step (8), the negative ion powder needs to be activated before use. The specific activation method is to add sodium hydroxide or sodium carbonate and react at 600-1000° C. for 60-120 minutes. The pressure per unit area of the pressing molding is 2-3 MPa.
[0024] In the above step (9), the drying temperature is 180-220° C., the drying time is 10-15 min, and then the temperature is quickly lowered to 100-120° C., and the drying time is 25-35 min.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The present invention adds negative ion powder to make the gypsum board have negative ions, and uses silica gel powder to make the paper-faced gypsum board have dense gaps, which can make the negative ion powder fully absorb external formaldehyde through these gaps. The improved foaming agent selected by the present invention can make the gypsum board more fluffy to the maximum extent, and the silica gel powder is evenly distributed on the gypsum board to make the negative ion distribution area wider. In addition, negative ions can also effectively absorb fine particles in the air, such as dust, bacteria and viruses, and deposit them on the ground through electrostatic action, thereby purifying the air.
[0027] 2. Titanium dioxide can convert ultraviolet energy into heat energy, which is absorbed. At the same time, under the irradiation of ultraviolet rays, formaldehyde can be decomposed into carbon dioxide and water. This conversion is completely harmless, which can effectively shield the gypsum board from ultraviolet rays and play a role in secondary absorption of formaldehyde. Titanium dioxide absorbs formaldehyde by photocatalytic reaction with ultraviolet rays. This absorption method is recyclable, which can slow down the consumption of negative ions and accelerate the release of negative ions. The concentration of negative ions released by the gypsum board of the present invention can reach 5387 / cm 3 .
[0028] 3. The adhesion of the glue powder is improved by activating and modifying the glue powder. The adhesion effect of the glue powder is improved in combination with the effect of plant starch. The use of a water reducer makes the gypsum board have high strength performance. The gypsum board is made more fluffy by improving the foaming agent. A non-ionic surfactant is added to the improved foaming agent as a foam stabilizer to increase the foaming effect of the foaming agent. While ensuring the strength of the gypsum board, the toughness of the gypsum board is ensured, and the problems of paper falling off and low strength of the gypsum board are solved. The addition of a retarder can prevent the gypsum board from splitting due to too fast solidification during molding, thereby ensuring the quality of the gypsum board and thus increasing its life.
[0029] 4. The materials used in the present invention are all environmentally friendly materials, non-toxic, and have little damage to the human body. They can ensure the purification of their own formaldehyde and effectively absorb formaldehyde in the air, thereby improving the performance and being beneficial to the physical and mental health of the user. Moreover, a certain amount of fly ash is added to the raw materials of the paper-faced gypsum board, which saves the use of materials and makes full use of resources.
[0030] In summary, the paper-faced gypsum board of the present invention has a long service life, high strength, good toughness, energy saving and environmental protection, and is suitable for promotion and use. DETAILED DESCRIPTION
[0031] The present invention is further described below by examples and comparative examples. However, it should be understood that the examples are used to explain the embodiments of the present invention, and the protection scope of the present invention is not limited by the examples within the scope of the subject matter of the present invention.
[0032] Embodiment 1:
[0033] A gypsum board comprises the following raw materials in parts by weight: 65 parts of semi-hydrated gypsum, 12 parts of fly ash, 12 parts of silica gel, 8 parts of tourmaline powder, 8 parts of titanium dioxide, 0.1 parts of improved foaming agent, 0.2 parts of water reducing agent, 1.5 parts of retarder, 3 parts of plant starch, 2.5 parts of activated rubber powder and 45 parts of water;
[0034] The improved foaming agent is composed of ethoxylated sodium alkyl sulfate, sodium α-olefin sulfonate, sodium xylene sulfonate and a foam stabilizer in a weight ratio of 1:1:1:0.1; the foam stabilizer is composed of fatty acid monoethanolamide and fatty alcohol polyoxyethylene ether in a weight ratio of 1:1;
[0035] The water reducing agent is composed of melamine and calcium lignin sulfonate in a weight ratio of 1:5;
[0036] The retarder is composed of sodium citrate and malic acid in a weight ratio of 1:1;
[0037] The plant starch is wheat starch, and the particle size of the wheat starch is 80 to 300 meshes.
[0038] The preparation method is carried out according to the following steps:
[0039] (1) Grinding the fly ash through a grinder and passing it through an 80-mesh sieve to obtain fly ash powder for later use;
[0040] (2) Preparation of activated rubber powder: Add rubber powder to 10% sodium carboxymethyl cellulose solution and react for 36 hours, filter to obtain pretreated rubber powder, then add 1% aqueous aziridine crosslinking agent and stir evenly, react for 1 hour to obtain activated colloid, wash with water, dry at 65°C, pulverize and pass through a 100-mesh sieve to obtain activated rubber powder for later use;
[0041] (3) taking silica gel, soaking it in dilute nitric acid at a volume ratio of 1:1 for 12 hours, then washing it with water until it is neutral, then soaking it in dilute hydrochloric acid at a volume ratio of 1:1 for 5 hours after shaking, then washing it with water until it is neutral, washing it with acetone to remove organic impurities, filtering it, drying it at 150-160° C. for 3 hours, grinding it to powder and passing it through a 100-mesh sieve to obtain silica gel powder for later use;
[0042] (4) After grinding the semi-hydrated gypsum through an 80-mesh sieve, add fly ash powder and silica gel powder, stir evenly, add water and stir to form gypsum slurry to obtain product A, which is set aside;
[0043] (5) Take the improved foaming agent and half the amount of water in the formula and mix them evenly to obtain Product B, which is set aside;
[0044] (6) Mix the retarder, plant starch and activated rubber powder with half the amount of water and stir evenly to obtain product C, which is set aside;
[0045] (7) Add titanium dioxide, water reducing agent, product B, and product C to gypsum slurry A in sequence, and stir at 300 rpm for 35 min to obtain gypsum slurry for later use;
[0046] (8) After the upper and lower papers are unwound, they enter the molding machine through an automatic deviation correcting machine. Before the gypsum slurry in the mixer enters the molding machine, negative ion powder is added, and the gypsum slurry falls onto the lower paper on the vibration platform and enters the molding machine, where the gypsum board is extruded out of the molding machine; the negative ion powder needs to be activated before use, and the specific activation method is to add sodium hydroxide or sodium carbonate and react at 800° C. for 90 minutes. The pressure per unit area of the pressing molding is 2 MPa;
[0047] (9) The formed gypsum board is solidified on the transport track and cut into gypsum board by a cutting machine. The cut gypsum board is sent to a dryer and dried at 200°C for 12 minutes, and then quickly cooled to 110°C and dried for 30 minutes to obtain a negative ion gypsum board.
[0048] Embodiment 2:
[0049] A gypsum board comprises the following raw materials in parts by weight: 70 parts of semi-hydrated gypsum, 10 parts of fly ash, 10 parts of silica gel, 10 parts of tourmaline powder, 5 parts of titanium dioxide, 0.05 parts of improved foaming agent, 0.5 parts of water reducing agent, 2 parts of retarder, 5 parts of plant starch, 2 parts of activated rubber powder and 50 parts of water;
[0050] The improved foaming agent is composed of ethoxylated sodium alkyl sulfate, sodium α-olefin sulfonate, sodium xylene sulfonate and a foam stabilizer in a weight ratio of 2:1:0.5:0.2; the foam stabilizer is composed of fatty acid monoethanolamide and fatty alcohol polyoxyethylene ether in a weight ratio of 2:1;
[0051] The water reducing agent is composed of melamine and calcium lignin sulfonate in a weight ratio of 2:5;
[0052] The retarder is composed of sodium citrate and malic acid in a weight ratio of 5:1;
[0053] The plant starch is corn starch, and the particle size of the corn starch is 80 to 300 meshes.
[0054] The preparation method is carried out according to the following steps:
[0055] (1) Grinding the fly ash through a grinder and passing it through an 80-mesh sieve to obtain fly ash powder for later use;
[0056] (2) Preparation of activated rubber powder: putty rubber powder is added to 10% sodium carboxymethyl cellulose solution and reacted for 48 hours, filtered to obtain pretreated rubber powder, and then 1% aqueous aziridine crosslinking agent is added and stirred evenly, reacted for 0.5 hours to obtain activated colloid, washed with water, dried at 65°C, crushed and passed through a 100-mesh sieve to obtain activated rubber powder for later use;
[0057] (3) taking silica gel, soaking it in dilute nitric acid at a volume ratio of 1:1 for 10-12 hours, then washing it with water until it is neutral, then soaking it in dilute hydrochloric acid at a volume ratio of 1:1 for 5 hours with shaking, then washing it with water until it is neutral, washing it with acetone to remove organic impurities, filtering it, drying it at 150-160° C. for 3 hours, grinding it to powder and passing it through a 100-mesh sieve to obtain silica gel powder for later use;
[0058] (4) After grinding the semi-hydrated gypsum through an 80-mesh sieve, add fly ash powder and silica gel powder, stir evenly, add water and stir to form gypsum slurry to obtain product A, which is set aside;
[0059] (5) Take the improved foaming agent and half the amount of water in the formula and mix them evenly to obtain Product B, which is set aside;
[0060] (6) Mix the retarder, plant starch and activated rubber powder with half the amount of water and stir evenly to obtain product C, which is set aside;
[0061] (7) Add titanium dioxide, water reducing agent, product B, and product C to gypsum slurry A in sequence, and stir at 200 rpm for 40 min to obtain gypsum slurry for later use;
[0062] (8) After the upper and lower papers are unwound, they enter the molding machine through an automatic deviation correcting machine. Before the gypsum slurry in the mixer enters the molding machine, negative ion powder is added, and the gypsum slurry falls onto the lower paper on the vibration platform and enters the molding machine, where the gypsum board is extruded. The negative ion powder needs to be activated before use. The specific activation method is to add sodium hydroxide or sodium carbonate and react at 600° C. for 120 minutes. The pressure per unit area of the pressing molding is 3 MPa.
[0063] (9) The formed gypsum board is solidified on the transport track and cut into gypsum board by a cutting machine. The cut gypsum board is sent to a dryer and dried at 180°C for 15 minutes, then quickly cooled to 120°C and dried for 25 minutes to obtain a negative ion gypsum board.
[0064] Embodiment 3:
[0065] A gypsum board comprises the following raw materials in parts by weight: 60 parts of semi-hydrated gypsum, 15 parts of fly ash, 15 parts of silica gel, 5 parts of tourmaline powder, 10 parts of titanium dioxide, 0.2 parts of improved foaming agent, 0.1 parts of water reducing agent, 1 part of retarder, 2 parts of plant starch, 3 parts of activated rubber powder and 40 parts of water;
[0066] The improved foaming agent is composed of ethoxylated sodium alkyl sulfate, sodium α-olefin sulfonate, sodium xylene sulfonate and a foam stabilizer in a weight ratio of 1:2:1:0.05; the foam stabilizer is composed of fatty acid monoethanolamide and fatty alcohol polyoxyethylene ether in a weight ratio of 1:2;
[0067] The water reducing agent is composed of melamine and calcium lignin sulfonate in a weight ratio of 1:10;
[0068] The retarder is composed of sodium citrate and malic acid in a weight ratio of 1:5;
[0069] The plant starch is potato starch, and the particle size of the potato starch is 80 to 300 meshes.
[0070] The preparation method is carried out according to the following steps:
[0071] (1) Grinding the fly ash through a grinder and passing it through an 80-mesh sieve to obtain fly ash powder for later use;
[0072] (2) Preparation of activated rubber powder: putty rubber powder is added to 10% sodium carboxymethyl cellulose solution and reacted for 24 hours, filtered to obtain pretreated rubber powder, and then 1% aqueous aziridine crosslinking agent is added and stirred evenly, reacted for 1.5 hours to obtain activated colloid, washed with water, dried at 65°C, crushed and passed through a 100-mesh sieve to obtain activated rubber powder for later use;
[0073] (3) taking silica gel, soaking it in dilute nitric acid at a volume ratio of 1:1 for 10-12 hours, then washing it with water until it is neutral, then soaking it in dilute hydrochloric acid at a volume ratio of 1:1 for 5 hours with shaking, then washing it with water until it is neutral, washing it with acetone to remove organic impurities, filtering it, drying it at 150-160° C. for 3 hours, grinding it to powder and passing it through a 100-mesh sieve to obtain silica gel powder for later use;
[0074] (4) After grinding the semi-hydrated gypsum through an 80-mesh sieve, add fly ash powder and silica gel powder, stir evenly, add water and stir to form gypsum slurry to obtain product A, which is set aside;
[0075] (5) Take the improved foaming agent and half the amount of water in the formula and mix them evenly to obtain Product B, which is set aside;
[0076] (6) Mix the retarder, plant starch and activated rubber powder with half the amount of water and stir evenly to obtain product C, which is set aside;
[0077] (7) Add titanium dioxide, water reducing agent, product B, and product C to gypsum slurry A in sequence, and stir at 400 rpm for 30 min to obtain gypsum slurry for later use;
[0078] (8) After the upper and lower papers are unwound, they enter the molding machine through an automatic deviation correcting machine. Before the gypsum slurry in the mixer enters the molding machine, negative ion powder is added, and the gypsum slurry falls onto the lower paper on the vibration platform and enters the molding machine, where the gypsum board is extruded out of the molding machine; the negative ion powder needs to be activated before use, and the specific activation method is to add sodium hydroxide or sodium carbonate and react at 1000° C. for 60 minutes. The pressure per unit area of the pressing molding is 2 MPa;
[0079] (9) The formed gypsum board is solidified on the transport track and cut into gypsum board by a cutting machine. The cut gypsum board is sent to a dryer and dried at 120°C for 10 minutes, and then quickly cooled to 100°C and dried for 35 minutes to obtain a negative ion gypsum board.
[0080] Embodiment 4:
[0081] A gypsum board comprises the following raw materials in parts by weight: 65 parts of semi-hydrated gypsum, 15 parts of fly ash, 12 parts of silica gel, 7 parts of tourmaline powder, 9 parts of titanium dioxide, 0.15 parts of improved foaming agent, 0.3 parts of water reducing agent, 1.5 parts of retarder, 3.5 parts of plant starch, 2.5 parts of activated rubber powder and 45 parts of water;
[0082] The improved foaming agent is composed of ethoxylated sodium alkyl sulfate, sodium α-olefin sulfonate, sodium xylene sulfonate and a foam stabilizer in a weight ratio of 1.5:1:0.8:0.05; the foam stabilizer is composed of fatty acid monoethanolamide and fatty alcohol polyoxyethylene ether in a weight ratio of 1:1;
[0083] The water reducing agent is composed of melamine and calcium lignin sulfonate in a weight ratio of 1:8;
[0084] The retarder is composed of sodium citrate and malic acid in a weight ratio of 1:2;
[0085] The plant starch is wheat starch and corn starch (the mass ratio of wheat starch to corn starch is 1:1), and the particle sizes of the wheat starch and corn starch are 80-300 meshes.
[0086] The preparation method is carried out according to the following steps: same as Example 1.
[0087] Embodiment 5:
[0088] A gypsum board comprises the following raw materials in parts by weight: 67 parts of semi-hydrated gypsum, 14 parts of fly ash, 13 parts of silica gel, 9 parts of tourmaline powder, 6 parts of titanium dioxide, 0.2 parts of improved foaming agent, 0.4 parts of water reducing agent, 2 parts of retarder, 3 parts of plant starch, 3 parts of activated rubber powder and 50 parts of water;
[0089] The improved foaming agent is composed of ethoxylated sodium alkyl sulfate, sodium α-olefin sulfonate, sodium xylene sulfonate and a foam stabilizer in a weight ratio of 2:1.5:0.5:0.1; the foam stabilizer is composed of fatty acid monoethanolamide and fatty alcohol polyoxyethylene ether in a weight ratio of 1:1;
[0090] The water reducing agent is composed of melamine and calcium lignin sulfonate in a weight ratio of 1:7;
[0091] The retarder is composed of sodium citrate and malic acid in a weight ratio of 1:1;
[0092] The plant starch is corn starch and potato starch (the mass ratio of corn starch to potato starch is 1:1), and the particle sizes of the corn starch and potato starch are 80-300 meshes.
[0093] The preparation method is carried out according to the following steps: same as Example 1.
[0094] Comparative Example 1:
[0095] The difference from Example 1 is that tourmaline powder is not added.
[0096] Comparative Example 2:
[0097] The difference from Example 1 is that no activated tourmaline powder is used, and the tourmaline powder is directly crushed and used.
[0098] Comparative Example 3:
[0099] The difference from Example 1 is that no titanium dioxide is added.
[0100] Comparative Example 4:
[0101] The difference from Example 1 is that no silica gel is added.
[0102] Comparative Example 5:
[0103] The difference from Example 1 is that in step (3), silica gel is directly dried at 150-160° C. for 3 hours, ground into powder and passed through a 100-mesh sieve to obtain silica gel powder, without acidification and impurity removal.
[0104] Comparative Example 6:
[0105] The difference from Example 1 is that the foaming agent used is only ethoxylated sodium alkyl sulfate.
[0106] Experimental Example 1: Negative ion release
[0107] The 12 mm thick gypsum board prepared by the methods of Examples 1-5 and Comparative Examples 1-5 was tested for negative ion release according to the method of JC / T1016-2006. The test results are shown in Table 1.
[0108] Table 2: Negative ion release test results
[0109]
[0110]
[0111] As can be seen from Table 1, the negative ion release concentration of the gypsum board without adding negative ion powder is only 657 / cm 3 After adding the negative ion powder, the negative ion release capacity of the gypsum boards prepared in Examples 1-5 is significantly enhanced; in particular, in Example 1, the negative ion powder is activated in a specific manner according to a specific ratio, and the use of silica gel powder and titanium dioxide is combined, so that the negative ion release capacity of the prepared gypsum board is significantly better, and the indoor negative ion concentration can be greater than 5000 / cm 3 Although the negative ion concentration of the gypsum board decreased after 3 months, the negative ion concentration in the room was still > 5000 / cm 3 , which is higher than the negative ion concentration of Examples 2-5. Therefore, the air quality of the space where the gypsum board is placed according to the index of Example 1 is significantly better than that of Examples 2-5, indicating that the gypsum board prepared in Example 1 has the best effect of releasing negative ions.
[0112] Compared with Example 2, in Example 1, the negative ion powder was not subjected to alkali activation treatment, and the activity of the negative ion powder was not high, the release capacity was insufficient, and the negative ion concentration could only reach 4000, which was much lower than the negative ion concentration of Example 1; and in Example 3, titanium dioxide was not added, which could not accelerate the absorption and conversion of formaldehyde, thereby slowing down the release rate of negative ions, and after three months, the negative ion release concentration was only 2388 / cm 3 , while Comparative Example 4 did not add silica gel, resulting in insufficient void density of the gypsum board, and the inability to quickly and effectively release negative ions. Comparative Example 5 used silica gel that was not acid-activated, and Comparative Example 6 used only ethoxylated alkyl sodium sulfate as the foaming agent, and their void density was not as good as that of Example 1, and the concentration of released negative ions was not as good as that of Example 1. Therefore, it is shown that the distribution of the negative ion powder in the gypsum board prepared in Example 1 is more reasonable, and the role of the negative ion powder in the gypsum board can be better exerted.
[0113] Experimental Example 2: Performance Test
[0114] The 12 mm thick gypsum boards prepared by the methods of Examples 1-5 and Comparative Examples 4 and 6 were tested for performance according to the method specified in GB / T9775-2008 "Gypsum Board". The test was performed three times and the average value was taken. The test results are shown in Table 2.
[0115] Table 2: Breaking load performance test results
[0116]
[0117] It can be seen from the results measured in Examples 1-5 that the mechanical properties of the gypsum board can meet the industry standards, while the mechanical properties of Comparative Examples 4 and 6 without adding silica gel and using improved foaming agents can also meet the industry standards, but are far lower than those of Examples 1-5.
Claims
1. An environmentally friendly negative ion paper-faced gypsum board, characterized in that: The negative ion paper-faced gypsum board includes a core material and a facing paper. The core material formula is calculated by weight: it is prepared from 60-70 parts of semi-hydrated gypsum, 10-15 parts of fly ash, 10-15 parts of silica gel, 5-10 parts of negative ion powder, 5-10 parts of titanium dioxide, 0.05-0.2 parts of improved foaming agent, 0.1-0.5 parts of water reducer, 1-2 parts of retarder, 2-5 parts of plant starch, 2-3 parts of activated rubber powder and 40-50 parts of water.
2. The environmentally friendly negative ion paper-faced gypsum board according to claim 1, characterized in that: The negative ion powder is tourmaline powder.
3. The environmentally friendly negative ion paper-faced gypsum board according to claim 1, characterized in that: The improved foaming agent is composed of ethoxylated sodium alkyl sulfate, sodium α-olefin sulfonate, sodium xylene sulfonate and a foam stabilizer in a weight ratio of 1-2:1-2:0.5-1:0.05-0.2; the foam stabilizer is composed of fatty acid monoethanolamide and fatty alcohol polyoxyethylene ether in a weight ratio of 1-2:1-2.
4. The environmentally friendly negative ion gypsum board according to claim 1, characterized in that: The water reducing agent is composed of melamine and calcium lignin sulfonate in a weight ratio of 1-2:5-10.
5. The environmentally friendly negative ion gypsum board according to claim 1, characterized in that: The retarder is composed of sodium citrate and malic acid in a weight ratio of 1-5:1-5.
6. The environmentally friendly negative ion gypsum board according to claim 1, characterized in that: The plant starch is one or more of wheat starch, corn starch and potato starch, and the particle size of the plant starch is 80-300 meshes.
7. The method for preparing the environment-friendly negative ion gypsum board according to any one of claims 1 to 6, characterized in that: The preparation method is carried out according to the following steps: (1) Grinding the fly ash through a grinder and passing it through an 80-mesh sieve to obtain fly ash powder for later use; (2) Preparation of activated rubber powder: Add putty rubber powder to 10% sodium carboxymethyl cellulose solution and react for 24h-48h, filter to obtain pretreated rubber powder, then add 1% aqueous aziridine crosslinking agent and stir evenly, react for 0.5-1.5h to obtain activated colloid, wash with water, dry at 65°C, crush through a 100-mesh sieve to obtain activated rubber powder, and set aside; (3) taking silica gel, soaking it in dilute nitric acid at a volume ratio of 1:1 for 10-12 hours, then washing it with water until it is neutral, then soaking it in dilute hydrochloric acid at a volume ratio of 1:1 for 5 hours with shaking, then washing it with water until it is neutral, washing it with acetone to remove organic impurities, filtering it, drying it at 150-160° C. for 3 hours, grinding it to powder and passing it through a 100-mesh sieve to obtain silica gel powder for later use; (4) After grinding the semi-hydrated gypsum through an 80-mesh sieve, add fly ash powder and silica gel powder, stir evenly, add water and stir to form gypsum slurry to obtain product A, which is set aside; (5) Take the improved foaming agent and half the amount of water in the formula and mix them evenly to obtain Product B, which is set aside; (6) Mix the retarder, plant starch and activated rubber powder with half the amount of water and stir evenly to obtain product C, which is set aside; (7) Add titanium dioxide, water reducing agent, product B, and product C to gypsum slurry A in sequence, stir evenly to obtain gypsum slurry, and set aside; (8) After the upper and lower papers are unwound, they enter the molding machine through an automatic deviation correcting machine. Negative ion powder is added to the gypsum slurry in the mixer before entering the molding machine, and the gypsum slurry falls onto the lower paper on the vibrating platform and enters the molding machine, where the gypsum board is extruded; (9) The formed gypsum board is solidified on the transport track and cut into gypsum board by a cutting machine. The cut gypsum board is sent to a dryer for drying to obtain negative ion gypsum board.
8. The method for preparing the environmentally friendly negative ion gypsum board according to claim 7, characterized in that: In the step (7), the stirring speed is 200-400 rpm, and the stirring time is 30-40 minutes.
9. The method for preparing the environmentally friendly negative ion paper-faced gypsum board according to claim 7, characterized in that: In the step (8), the negative ion powder needs to be activated before use. The specific activation method is to add sodium hydroxide or sodium carbonate and react at 600-1000° C. for 60-120 minutes. The pressure per unit area of the pressing molding is 2-3 MPa.
10. The method for preparing the environmentally friendly negative ion gypsum board according to claim 7, characterized in that: In the step (9), the drying temperature is 180-220° C., the drying time is 10-15 min, and then the temperature is quickly lowered to 100-120° C., and the drying time is 25-35 min.